A rare confluence: chronic myeloid leukemia in a pediatric case of beta thalassemia - Agrawal, Preeti; Raghavan, Lavanya; Mittal, Arpit (International Journal of Contemporary Pediatrics, 2026)
Chronic myeloid leukemia (CML) is rare in children and extremely uncommon in patients with underlying hemoglobinopathies such as beta thalassemia. This report describes a 12‑year‑old beta thalassemia patient, who presented with fever, pallor and weakness, and was found to have marked hepatosplenomegaly and leukocytosis. Peripheral blood showed leukocytosis with increased myeloid precursors and bone marrow evaluation showed hypercellular marrow with myeloid hyperplasia and basophilia, consistent with a chronic myeloproliferative neoplasm. Karyotyping revealed balanced reciprocal translocation t (9;22) and reverse‑transcriptase polymerase chain reaction (RT‑PCR) detected BCR‑ABL1 p210 fusion transcript, confirming the diagnosis of chronic phase CML in a background of beta thalassemia. The patient had elevated serum ferritin, indirect hyperbilirubinemia and mildly deranged transaminases, attributable to chronic transfusions and iron overload. After initiation of appropriate therapy, leukocyte counts normalized within one month along with disappearance of circulating immature myeloid precursors. This case highlights the importance of maintaining a high index of suspicion for CML in thalassemic patients with unexplained leukocytosis and splenomegaly, and underscores the need for integrated morphologic, cytogenetic and molecular work-up to distinguish disease progression from a second primary hematologic malignancy.